2018
DOI: 10.1007/s10792-018-0848-8
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Pupillary Block After Retinal Detachment Surgery in an Eye with Toric Implantable Collamer Lens

Abstract: Reverse pupillary block, after dilation is an unusual phenomenon, which was seen in a silicone-filled eye with toric ICL implant. In cases of inflammatory debris blocking Aquaport opening of ICL, conservative management with topical steroids and antiglaucoma medications can help reduce inflammation and IOP, alleviating need for any intervention, such as laser iridotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
2
3
0
Order By: Relevance
“…We know from our experiments that CLR is negatively correlated with the postoperative vault, which is consistent with previous studies [ 18 , 23 , 24 ]. The authors reported that the mean CLR of the low vault group (< 100 μm) was higher than that of the high vault group (> 750 μm) [ 23 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…We know from our experiments that CLR is negatively correlated with the postoperative vault, which is consistent with previous studies [ 18 , 23 , 24 ]. The authors reported that the mean CLR of the low vault group (< 100 μm) was higher than that of the high vault group (> 750 μm) [ 23 ].…”
Section: Discussionsupporting
confidence: 94%
“…We know from our experiments that CLR is negatively correlated with the postoperative vault, which is consistent with previous studies [ 18 , 23 , 24 ]. The authors reported that the mean CLR of the low vault group (< 100 μm) was higher than that of the high vault group (> 750 μm) [ 23 ]. Wang et al [ 25 ] found that the correlation coefficient between CLR and the 1-year postoperative vault was − 0.509, which was close to the correlation coefficient ( − 0.505) between CLR and the 6-month postoperative vault in this study.…”
Section: Discussionsupporting
confidence: 94%
“…At present, the central hole ICL can reduce the incidence of pupillary block, eliminates the need for laser peripheral iridectomy preoperatively and obtains satisfactory IOP after surgery [146][147][148][149][150][151]. In particular, Gonzalez-Lopez [152], Mansoori T [153], Isha G [154] and Frost A et al [155] had all reported pupillary block glaucoma secondary to central hole obstruction after ICL implantation, which may be related to viscoelastic residue, iris pigmentation, increase in inflammatory factors in aqueous humor and so on. The longest occurrence was 5 years after ICL implantation.…”
Section: Loss Of Corneal Endothelial Cells and Corneal Decompensationmentioning
confidence: 99%
“…High intraocular pressure after ICL implantation may be caused by the following factors: pupil block due to lens diameter or thickness [18], the aqueous humor returning to the vitreous cavity [19], pigment dissemination [20], hormone correlation [21], intraoperative viscoelastic residue [22], or pre-existing openangle glaucoma [23]. There was no signi cant difference between the two groups (P > 0.05, Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…3, A,B); therefore, there was no case of reduced arch height and high IOP. Mansoori et al [23] presented a case of high IOP secondary to PPV, after v4C ICL implantation was complicated by rhegmatogenous retinal detachment. The reason may be that in ammatory factors blocked the "central hole," which is similar to pupil block.…”
Section: Discussionmentioning
confidence: 99%